Pandemi Covid-19 Dan Kas Di Tangan - Salma Faundria Nagari; Ari Budi Kristanto (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to test whether the impact of the Covid-19 pandemic has an effect on increasing company’s cash on hand. The data used in this study are secondary data in the form of annual financial reports for the 2019-2020 period and information disclosure reports related to the impact of the 2020 Covid-19 pandemic on manufacturing companies listed on the Indonesia Stock Exchange. The method used to determine the data sample is purposive sampling technique. This research is a descriptive study with a quantitative approach, and uses data analysis techniques in the form of multiple linear regressions. The results obtained indicate that the impact of the Covid-19 pandemic has a negative effect on changes in the increase in the value of cash in the company. The findings of this study are expected to be considered for investors and potential investors regarding the return on their investment decisions for manufacturing companies affected by the crisis, namely the Covid-19 pandemic. Another expected benefit is to add to the literature in the academic field that discusses the impact of the Covid-19 pandemic on changes in the increase in cash on hand in manufacturing companies listed on the Indonesia Stock Exchange. Keywords: Covid-19 pandemic, Covid-19 Pandemic Impact, Cash on Hand, Manufacturing Companies